EVALUASI STABILITAS FARMASETIK DAN UJI IRITASI FORMULA MASKER SARI LEMON (Citrus limon L.) DENGAN YOGURT PLAIN - Iskandar Zulkarnain; Ermina Pakki; Mirawati Mirawati; Arin Rizki Talib (Fakultas Farmasi UMI, 2018)
The use of lemon juice and yogurt can provide good care for facial skin, so have the potential to be formulated into a mask to overcome skin problems. The study aimed to produce a mask dosage froms formula pharmaceutically stable and not irritating. The lemon juice extract was obtained by using freeze-drying, and optimization of anionic emulgator (TEA-Stearate) and nonionic emulgator (Tween-Span 60) are carried out. The formulation was continued with the variations in lemon extract concentrations of 0.5; 1; and 2% w/v by evaluating the physical characteristics and stability with parameters including organoleptic examination (smell, color, and consistency), centrifugation, homogeneity, pH, type of emulsion, drying time, dispersion, viscosity, and determination of flow type before and after conditions are forced at 5oC and 35oC for the 10 cycles for irritation testing using test rabbits. The results showed that the formula with an anionic emulgator (TEA-stearic) of 1:2% b/v with a lemon extract concentration of 1% was a pharmaceutically stable formula and the irritation the results showed that the formula with a lemon extract of 0.5% and 1% b/v did not cause any irritation.